Implementasi Nilai-Nilai Pancasila di Panti Asuhan Sahabat Keluarga Indonesia - Ema Serika Br Ginting; Nadratul Aini Lubis; Ruth Sahana Manalu; Pristi Suhendro Lukitoyo (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Indonesian Family Friends Orphanage (PASKI) is a social institution committed to caring for and educating orphaned and underprivileged children based on the values of Pancasila. The implementation of Pancasila values at PASKI is clearly visible in various aspects of orphanage life, starting from interactions between foster children, caregivers, to orphanage staff. Indonesian Family Friends Orphanage (PASKI) implements Pancasila values in various aspects of orphanage life, starting from interactions between foster children, caregivers, to orphanage staff. This implementation is clearly visible in religious activities, character education, and decision making. The application of Pancasila values in PASKI has a positive impact on the development of foster children. Foster children grow up to be individuals who believe, have noble character, and have a sense of love for their country. They also have sufficient knowledge and skills to face life in the future. It is hoped that the implementation of Pancasila values in PASKI can help children grow into individuals with noble character, a nationalist spirit, and ready to contribute to the nation and state.